SYMMETRIC POLYNOMIALS AND FUNCTIONS OF TRIANGULAR MATRICES (TABLES) - Goy, T. P.; Zatorsky, R. A.; Lishchynsky І. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Using the functions of triangular matrices (tables), we established formulas for members of high order linear homogeneous recurrence. Consequently, we obtained some connection formulas between symmetric polynomials.